Pembelajaran Berdiferensiasi Dalam Mata Pelajaran Seni Budaya Pada Era Distrupsi - Ida Bagus Alit Arta Wiguna; A.A. Gede Oka (Widya Sundaram : Jurnal Pendidikan Seni Dan Budaya, 2023)
Differentiated learning refers to an approach to learning that is tailored to the needs, interests, abilities and learning styles of individual students. Differentiated learning encourages and values diversity in the classroom. It helps improve student motivation, participation and learning outcomes. This research aims to find differentiated learning that is suitable for arts and culture subjects in the era of distrusion so that teachers are able as facilitators in the classroom to provide learning that suits students. this research the author uses qualitative research methods, the research approach used is library research. The data collection techniques used are recording data taken from various sources of written materials and then identifying contextual evidence, namely by looking for relationships between data and the reality that the author examines. The results of this study are 1). Recognising student diversity in interests, abilities, and learning styles, and understanding individual student differences. 2). Customising the cultural arts curriculum to meet individual student needs, be it in content, teaching methods, or the level of difficulty of the material. Use a variety of teaching strategies that suit students' needs, such as direct teaching, group discussion, problem solving, group work, or inquiry-based projects. 3). Adopting differentiated assessment, allowing students to demonstrate student understanding in a way that suits students' strengths and preferences.